Which Way, Amina ? - Ade-Ajayi, Christie (Macmillan Nigeria Publishers Ltd, 2001)
Amina becomes part of the Yakubu family as a baby. she gets a lot of love and attention until her mother has a set of twins.Then,she turns to some friends at school. What does she learn from them?What happens to her in the end? Find out as you read the rest of the story.
Keywords: Growing Up; Adventure; Juvenile Fiction